Population Dynamics of Mackerel Scad (Decapterus macarellus) Landed at the Sibolga Archipelago Fishing Port - Hairul Umam; Ricky Winrison Fuah; Rosi Rahayu; Muhammad (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This study analyzed the population dynamics of mackerel scad (Decapterus macarellus) landed at the Sibolga Archipelago Fishing Port, North Sumatra, Indonesia, to assess growth, mortality, recruitment, and exploitation status. Length–frequency data from 200 specimens were analyzed using the FISAT II software. The asymptotic length (L∞) and growth coefficient (K) were estimated at 40.4 cm TL and 0.51 year⁻¹, respectively, indicating a moderately fast-growing species typical of tropical small pelagics. The total, natural, and fishing mortalities were 3.91, 1.08, and 2.84 year⁻¹, resulting in an exploitation rate (E = 0.73), which exceeds the optimum level (Eopt = 0.5), signifying overexploitation. Recruitment analysis showed two annual peaks (March–April and September–October), reflecting a bimodal spawning pattern. The length at first capture (Lc = 16.2 cm TL) was smaller than the length at first maturity (Lm ≈ 17.0 cm TL), suggesting premature harvesting. The yield-per-recruit model indicated E₀.₁ = 0.607 and Emax = 0.749, reinforcing that the stock is fully exploited. These findings underscore the urgent need to regulate fishing pressure through mesh-size adjustments and seasonal closures to sustain D. macarellus fisheries in western Indonesian waters.